Patient perspectives on delays in care for kidney stones: A qualitative analysis - Ibukunoluwa I. Ibrahim; Daniel L. Zager; Leslie B. Charondo; Sophia Zamudio-Haas; Sara L. Ackerman; David B. Bayne (PLoS ONE, 2026)
Purpose Traditional insurance claims dataset analyses have exposed disparities in treatment delays for kidney stones along lines of socio-economic status, particularly among patients who are underinsured and/or racial/ethnic minorities. Analyzing patient experiences through qualitative semi-structured interviews allows for elucidation of common root causes leading to care delays in patients with kidney stones. Materials and methods 20 participants were recruited from a group of adult patients at a safety net hospital and academic medical center who had been referred for urological care after presenting to the Emergency Department for kidney stones. Patients were selected for semi-structured interviews if they failed to present to the urology clinic after 60 days of referral placement. Interviews were conducted in Spanish or English. Transcripts were coded and analyzed using thematic analysis. Results Of the 20 participants, the median age in years was 46 (range 22–72), 50% identified as female, 40% were White, 40% were Hispanic, 20% were Black, and 20% were Spanish-dominant. The median delay was 105 days. Thematic analysis identified patient-extrinsic obstacles in obtaining timely care in the form of care costs and skepticism from health care providers, such as perceptions of being drug-seeking or feigning pain. We further identified patient-intrinsic obstacles, such as gaps in understanding of the dangers of stone disease and difficulty navigating care coordination. Conclusions This study provides insights into multi-level factors that impact care delays for patients with kidney stone disease. Findings from this work deepen understanding of why patient experiences in care delays manifest along lines of socio-economic status and can inform future interventions to reduce disparities.